1999
DOI: 10.1097/00002508-199909000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-term Outcomes of Children with Complex Regional Pain Syndrome Type I Treated with Exercise Therapy

Abstract: Intense exercise therapy is effective in initially treating childhood CRPS and is associated with low rate of long-term symptoms or dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
191
3
32

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 314 publications
(236 citation statements)
references
References 20 publications
10
191
3
32
Order By: Relevance
“…Some reports suggest benefits of conservative interventions such as exercise, 76 transcutaneous electrical nerve stimulation, 77 percutaneous electrical nerve stimulation, 78 graded motor imagery 79 and cognitive behavioural therapy or supportive psychotherapy.…”
Section: Current Management Nonpharmacologicmentioning
confidence: 99%
“…Some reports suggest benefits of conservative interventions such as exercise, 76 transcutaneous electrical nerve stimulation, 77 percutaneous electrical nerve stimulation, 78 graded motor imagery 79 and cognitive behavioural therapy or supportive psychotherapy.…”
Section: Current Management Nonpharmacologicmentioning
confidence: 99%
“…Which of these pathophysiological changes mediates the bone changes is still a matter of dispute (11). The increased absorption of the tracer in bone scan may point to neurogenic inflammation, decreased sympathetic activity or bone demineralization caused by active bone metabolism (8,12). Bone scan may be used in determining patients who would benefit from biphosphonate therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Bone scan may be used in determining patients who would benefit from biphosphonate therapy. In contrast to adults, bone scans in children and adolescents display diffuse decreased tracer absorption in all three stages of the disorder, but bone scans with increased absorption have also been reported (10)(11)(12)(13)(14)(15). A study reported that among 103 children with CRPS, the bone scan of the affected area showed increased accumulation of the radiotracer in 31, decreased accumulation in 11, and normal absorption in the rest (14).…”
Section: Discussionmentioning
confidence: 99%
“…Reflex sympathetic dystrophy generally affects lower limbs and is rarely bilateral. 3,6,[8][9][10] Wilder et al 7 observed 70 children with RSD and found that 87% of episodes occurred in lower limbs and that 31% of the children exhibited events in more than one location.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9]12 Two studies 7,15 evaluated children with RSD, employing physiotherapy, TENS (transcutaneous electrical nerve stimulation) and psychotherapy, almost always associated with NHAI. This treatment was effective for around 70% of the patients, with significant functional improvements.…”
Section: Discussionmentioning
confidence: 99%